08 The Neologism Reception in Modern Times - Cristina Eva SAUCIUC (Association of Social and Educational Innovation, 2014)
Seen in its historical evolution, lexical innovation throughout the literary text illustrates through numerous acts of language efforts to enrich our modern culture with new lexical expressive elements. The ideas, imagination games has promotes terms and new words associations, proving, in this way, multiple possibilities to combine metaphoric words available in language. Understanding criterion without effort and the novelty must be accepted as a fundamental rule in the literary text, and due to the fact that science and literary art are to meet in unusual associations,constitute a basis and an incentive, at the same time, in the development and modernization of Romanian literary language.